Social Media Monitoring of Superpriority Destination Svargabumi Borobudur - Lydia Irena; Ananias Reszki; Septia Winduwati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Svargabumi has emerged as one of the premier tourism destinations in the Borobudur area, part of the Borobudur super-priority tourism destinations. Svargabumi offers a blend of natural beauty and a variety of Instagram-worthy photo spots, making it a popular attraction. Promoting such destinations through social media is recognized as one of the most effective ways to showcase cultural richness. However, social media promotion must be accompanied by monitoring to ensure strategic accuracy and evaluate public opinion and sentiment. This process, known as social media monitoring, faces the challenge of managing the vast volume of data generated by online activities. Therefore, appropriate tools are essential for this purpose, one of which is Brand24, which provides comprehensive analysis, including statistical data and detailed information on all related media coverage. The research question posed is how to analyze the social media monitoring of the super-priority destination Svargabumi Borobudur. This study aims to analyze the social media monitoring of Svargabumi Borobudur as a super-priority destination. Using a mixed-methods approach, the study seeks to produce comprehensive and objective data. The research subjects are public sentiment and opinions on social media about Svargabumi, with the key informant being Svargabumi’s Marketing Manager, referred to as A. The research object is the social media monitoring of the super-priority destination Svargabumi Borobudur. The data collection technique used in this study was the social media monitoring tool, Brand24. Social media monitoring using Brand24 revealed that Svargabumi has a significant digital presence on Instagram, the primary platform for discussions about the destination. Svargabumi also has significant economic value through mentions, with an estimated Advertising Value Equivalency (AVE) of 7,008. Positive sentiments, with 33 items, also dominated, indicating that Svargabumi has successfully built a strong digital reputation among tourists. Furthermore, user-generated content and contributions from micro- and nano-influencers are key elements in increasing audience exposure and engagement. However, engagement on platforms like TikTok and YouTube can still be improved to maximize potential reach.